CLINICO-PATHOLOGICAL SPECTRUM OF BIOPSY PROVEN NATIVE KIDNEY DISEASE IN A TERTIARY HOSPITAL IN NEPAL - Sedhain, Arun; Karki, Rabina; Baral, Anil; Khatri, Bikash; Piya, Albina; Aryal, Manoj; Karki, Abhishek (Journal of Chitwan Medical College, 2024)
Background: Kidney biopsy has been regarded as an important tool for the diagnosis, management and monitoring the prognosis of renal diseases. We conducted this study to find out the clinico-pathological spectrum by native kidney biopsy in a relatively large scale. Methods: This was a hospital based, prospective, observational study carried out in a tertiary hospital of Kathmandu from January 2022 to December 2023. The biopsy specimens were reported by nephropathologists on the basis of light microscopy, direct immunofluorescence for all samples and electron microscopic examination whenever indicated. The patient`s demographic profile, indication and histological findings of kidney biopsy were studied and analyzed using appropriate statistical tools. Results: A total of 610 kidney biopsies were performed during the study period, of which 24 samples did not meet the inclusion criteria and 586 patients were included in the final analysis. The mean age of the patients was 42.08 ±9.09 years and 59.03% of the patients were younger than 40 years. Females outnumbered the males with female to male ratio of 1.09. The most common presentation was limb swelling (81.22%) and nephrotic syndrome was the most common indication for the biopsy and the most common histological finding was lupus nephritis, followed by IgA nephropathy and FSGS. Non-diabetic kidney disease was found in 54.28% of diabetic patients who underwent biopsy. Conclusions: Nephrotic syndrome was the most common indication for kidney biopsy with lupus nephritis being the most common histological finding. Non diabetic kidney disease (NDKD) was found in more than half of the patients with diabetes mellitus.